Physiological responses that account for the increased power output in speed skating using klapskates - Houdijk, H.; Heijnsdijk, E. A.; de Koning, J. J.; de Groot, G.; Bobbert, M. F. (European Journal of Applied Physiology, 2000)
The present study investigates which physiological sources support the increase in mechanical power output (W˙out) that can be obtained using klapskates in speed skating. It was hypothesized that the increase in W˙out could be achieved through an increase in gross efficiency or an increase in aerobic power (W˙aer). Six speed skaters performed a submaximal and maximal 1600-m skating test with both klapskates and conventional skates, to measure gross efficiency and maximal W˙aer during speed skating. The rate of oxygen uptake (V˙O2) and post-exercise blood lactate concentrations ([La]) were measured and video recordings were made. W˙aer was calculated from V˙O2. W˙out was derived from the power needed to overcome air and ice friction. Gross efficiency was calculated as the ratio of W˙out and W˙aer. In the maximal tests, the subjects skated faster with klapskates compared to conventional skates (10.0 vs 9.6 m ·s-1). They sustained the resulting higher W˙out with klapskates with an equal V˙O2. [La] was, however, 1.7 mmol · l-1 higher when klapskates were used, which might reflect an increase in anaerobic power. During the submaximal tests the skaters generated equal W˙out with both types of skate. Although not statistically significant, V˙O2 and W˙aer were, on average, lower when klapskates were used compared to conventional skates [mean (SD) 0.3 (0.43) l · min-1, 105 (143) W]. Despite the lack of a statistically significant difference in W˙aer, gross efficiency was shown to be significantly higher with klapskates compared to conventional skates (16.3% vs 14.8%, P=0.02). We conclude that the increase in W˙out when the subjects were using klapskates could be explained by an increase in gross efficiency rather than an increase in W˙aer.